NMSSM from alternative deflection in generalized deflected anomaly mediated SUSY breaking - Xiaokang Du; Fei Wang (European Physical Journal C: Particles and Fields, 2018)
Abstract We propose a new approach to generate messenger–matter interactions in deflected anomaly mediated SUSY breaking mechanism from typical holomorphic messenger–matter mixing terms in the Kahler potential. This approach is a unique feature of AMSB and has no analog in GMSB-type scenarios. New coupling strengths from the scaling of the (already known) Yukawa couplings always appear in this approach. With messenger–matter interactions in deflected AMSB, we can generate a realistic soft SUSY breaking spectrum for next-to-minimal supersymmetric standard model (NMSSM). Successful electroweak symmetry breaking conditions, which is not easy to satisfy in NMSSM for ordinary AMSB-type scenario, can be satisfied in a large portion of parameter space in our scenarios. We study the relevant phenomenology for scenarios with (Bino-like) neutralino and axino LSP, respectively. In the case of axino LSP, the SUSY contributions to $$Δ a_μ $$ Δaμ can possibly account for the muon $$g-2$$ g-2 discrepancy. The corresponding gluino masses, which are found to below 2.2 TeV, could be tested soon at LHC.